Sexual Dimorphism in Jurassic Ammonites from the Queen Charlotte Islands - Hall, R. (Geoscience Canada, 1975)
Summary Certain pairs of ammonite "species", different in size and exhibiting contrasting morphology on their adult stages, are shown to possess inner whorls (earlier growth stages) which are almost identical in all morphological aspects. The similarities indicate close genetic relationship, the divergence in size and adult body chamber being secondary sexual characters. Five such dimorphic pairs occur together in the same strata in the Middle Jurassic Yakoun Formation on the Queen Charlotte Islands and It is suggested that they represent the two sexes.